A review of major flood events in Malaysia between 1970-2024 - Ahmad, Nordila; Ng, Choy Peng; Ismail, Neza; Wong, Mohd Muhaimin Ridwan; Abbas, Fuad; Law, Teik Hua; Zul Bahari, Ahmad Najman ‘Azam; Mohd Rofi, Muhamad Faisharulfaizi (National University of Malaysia, 2025)
This study compiles comprehensive data on significant flooding incidents throughout the historical narrative of Malaysia and presents the official estimates of flood-related losses for the chosen major flood occurrences spanning from 1970 to 2024. Additionally, it offers details regarding the underlying factors and consequences of floods, as well as an explanation of the flood prevention strategies implemented in this area. In addition, it provides information on the distribution of financial resources for flood mitigation initiatives by the Malaysian government as part of the Malaysia Plan (1971 to 2020). Past flood experiences have shown that a significant danger leading to potential loss of life or severe harm to individuals arises from the scale and strength of the floods, encompassing factors such as water levels, flow rates, and the speed at which the flood occurs. Intense floods characterised by elevated water levels and sudden occurrence, such as flash floods, have the potential to overwhelm flood defences and escape routes, hence increasing the risk of drowning and injuries. Nevertheless, it is recommended that Integrated Smart Alarm System will be deployed in flood-prone regions to decrease fatalities.